IDENTIFICATION OF DIFFERENT STRUCTURES FORMED DURING CROSSLINKING OF POLYETHYLENE WITH VINYL TRIETHOXYSILANE FTIR, Si 29 NMR AND XPS STUDY - Fuzail, M.; Shah, G. B.; Ahmed, I. (The Nucleus, 2010)
To bring about improvement in service temperature, mechanical and thermal properties of low density polyethylene, it was crosslinked with vinyltriethoxysilane in the presence of benzoyl peroxide. Identification of different structures which were formed as a result of crosslinking, was carried out by ATR/FTIR, Si 29 NMR and x-ray photoelectron spectroscopy (XPS). In this article, the effect of silane and peroxide concentrations on the types of different structures or grafts formed during crosslinking has been discussed. FTIR spectra show that Si-O-Si asymmetric stretching and Si-C stretching was observed in the general range 1000-1130 and 735-800 cm-1 respectively. Theoretical and experimental band assignments for Si 29 NMR spectra exhibit the presence of various fragments based on T0 , T1 , T2 and T3 structures. It has been found that for the maximum silane concentration, predominate form of crosslink is T3 i.e trioxygented silane with three silane bridges. XPS analysis further confirms the presence of variety of C, O and Si bonding in the silane crosslinked polyethylene which exhibit varied elemental ratios.